ADAR1 prevents autoinflammatory processes in the heart mediated by IRF7 - Garcia-Gonzalez, Claudia; Dieterich, Christoph; Maroli, Giovanni; Wiesnet, Marion; Wietelmann, Astrid; Li, Xiang; Yuan, Xuejun; Graumann, Johannes; Stellos, Konstantinos; Kubin, Thomas; Schneider, Andre; Braun, Thomas (Circulation research, 2022)
Background: - - ADAR1 (adenosine deaminase acting on RNA-1)-mediated adenosine to inosine (A-to-I) RNA editing plays an essential role for distinguishing endogenous from exogenous RNAs, preventing autoinflammatory ADAR1 also regulates cellular processes by recoding specific mRNAs, thereby altering protein functions, but may also act in an editing-independent manner. The specific role of ADAR1 in cardiomyocytes and its mode of action in the heart is not fully understood. To determine the role of ADAR1 in the heart, we used different mutant mouse strains, which allows to distinguish immunogenic, editing-dependent, and editing-independent functions of ADAR1. - - Methods: - - Different Adar1-mutant mouse strains were employed for gene deletion or specific inactivation of ADAR1 enzymatic activity in cardiomyocytes, either alone or in combination with Ifih1 (interferon induced with helicase C domain 1) or Irf7 (interferon regulatory factor 7) gene inactivation. Mutant mice were investigated by immunofluorescence, Western blot, RNAseq, proteomics, and functional MRI analysis. - - Results: - - Inactivation of Adar1 in cardiomyocytes resulted in late-onset autoinflammatory myocarditis progressing into dilated cardiomyopathy and heart failure at 6 months of age. Adar1 depletion activated interferon signaling genes but not NFκB (nuclear factor kappa B) signaling or apoptosis and reduced cardiac hypertrophy during pressure overload via induction of Irf7. Additional inactivation of the cytosolic RNA sensor MDA5 (melanoma differentiation-associated gene 5; encoded by the Ifih1 gene) in Adar1 mutant mice prevented activation of interferon signaling gene and delayed heart failure but did not prevent lethality after 8.5 months. In contrast, compound mutants only expressing catalytically inactive ADAR1 in an Ifih1-mutant background were completely normal. Inactivation of Irf7 attenuated the phenotype of Adar1-deficient cardiomyocytes to a similar extent as Ifih1 depletion, identifying IRF7 as the main mediator of autoinflammatory responses caused by the absence of ADAR1 in cardiomyocytes. - - Conclusions: - - Enzymatically active ADAR1 prevents IRF7-mediated autoinflammatory reactions in the heart triggered by endogenous nonedited RNAs. In addition to RNA editing, ADAR1 also serves editing-independent roles in the heart required for long-term cardiac function and survival.